A educação ambiental e a gestão de resíduos sólidos no Instituto Federal de Educação, ciência e tecnologia-campus São Cristóvão : realidade e perspectivas - Bispo, Mércia Mirian Gama (2011)
The need to work on environmental education in solid waste management in an educational institution allows for reflection, awareness, decision making, change attitudes and motivate people to participate effectively and responsibly in the conservation of the environment experienced daily. This paper aims to outline a proposal for the Environmental Education Program - SAP for solid waste management at the Federal Institute of Education, Science and Technology of Sergipe, Campus São Cristóvão, to minimize environmental impacts exist and offer better quality life of the community. The research was to focus on epistemic phenomenology, and used a methodology of qualitative and quantitative nature. Data were collected through bibliographic and documentary sources, interviews with the director general of the Institute and coordinator of the sector of solid waste management, through questionnaires distributed to students, teachers, administrative staff and third-party servers and performing characterizations of solid waste the Institute. As the main results of work can be noted that the Institute has managed solid waste so precarious and environmentally inadequate, especially with regard to their final destination. All solid waste generated at the Institute is deposited in an open place, where it is partially buried and / or burned, leading to contamination of soil, groundwater, air and the proliferation of vectors that endanger the health of the population and environmental sustainability site. There is no separate collection at the Institute implanted, only selective collectors in some strategic locations. It was evident through the characterization of waste within the Institute, a significant amount of potentially recyclable materials. In assessing the results of interviews and questionnaires there was a very significant commitment and participation of the community involved to minimize the environmental issue evidenced at the Institute. Finally the paper presents the design of a proposal to the Office of EAP of Sergipe - Campus São Cristovão, backed by a critical and emancipatory conception of education that has as its principle to reduce consumption and subsequently the reclassification of the waste for reuse and reuse. The program suggests, among other actions, the implementation of projects for separate collection, sorting units and composting of solid waste and environmental education programs permanent, focused on the issue of solid waste. Manage solid waste properly is essential for the Instituto Federal de Sergipe, which is the essence of their academic and professional teaching-an ethical commitment to a healthy and ecologically balanced environment.